Extension of use of lycopene (E 160d) to certain meat preparations, meat products and fruit and vegetable preparations. (1st December 2017) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present scientific opinion deals with the safety of the extension of use of lycopene (E 160d) in certain meat preparations, meat products and fruit and vegetable preparations. Lycopene (E 160d) is an authorised food additive in the EU for use in several food categories and an acceptable daily intake (ADI) of 0.5 mg/kg body weight (bw) per day was established. In the present opinion, the Panel decided that a comparison of the exposure resulting from the current uses and use levels with the exposure resulting from this additional proposed extension of uses would be sufficient to address the safety of lycopene. The Panel calculated that, considering the current maximum permitted levels (MPLs) and the proposed extension of uses and use levels, the mean dietary exposure to lycopene (E 160d) in the total population ranged from 0.01 mg/kg bw per day in infants to 0.82 mg/kg bw per day in toddlers. At the high level, dietary exposure to lycopene (E 160d) ranged from 0.03 mg/kg bw per day in infants to 1.39 mg/kg bw per day in toddlers. The Panel concluded that the proposed extension of uses of lycopene (E 160d) as a food additive in meat preparations, meat products and fruit and vegetable preparations up to 60 mg/kg would not add significantly to the intake of the food additive at its current MPL. However, the Panel noted that the overall intake at the MPL scenario would exceed the currently established ADI. The Panel acknowledged the uncertainties in the current estimates which could result in an overestimation of the exposure to lycopene (E 160d) as a food additive in European countries and therefore concluded that a refined exposure estimate would be recommended focusing on food categories contributing the most to its estimates, in order to decrease uncertainties in its current estimates.